Crowdfunding a monthly income: an analysis of the membership platform Patreon - Tobias Regner (Journal of Cultural Economics, 2020)
Membership platforms allow creators to crowdfund a monthly income, while campaigns on conventional reward crowdfunding portals aim to reach a specified funding target within a preset period. We study transaction-level data from Patreon, the biggest membership platform, to gain insights about behavioral patterns at this emerging type of crowdfunding. Our analysis shows that hundreds of creators crowdfund a sizable income (more than 2500 monthly). We also find that measures of communication quality are determinants of project success, in line with the related literature. Funding dynamics—pledges as well as deletions—are heterogeneous across campaigns. Our analysis suggests that the option to delete the monthly pledge to a creator at any time serves as a feedback mechanism. We conclude that crowdfunding a monthly income offers the creative class a viable alternative to advertising-based business models.
Keywords: D90; G23; L26; L82; L86; 330; Crowdfunding; Patreon; Funding dynamics; Cultural goods; Membership platform